2013
DOI: 10.1002/app.39464
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental study on the development of a surgical device for polymer‐tissue adhesion using vibration damping of polymeric materials

Abstract: To develop a surgical handheld device that can be used to promote polymer-tissue or tissue-tissue adhesion, we designed a polymeric clamp material (PCM) that self-heats as a result of vibration. By using the PCM, heat can be applied to the target biomaterial and the tissue simultaneously. The optimal temperature is high enough to promote adhesion but low enough to retain the native tissue's integrity. Furthermore, the PCM should not adhere to the target polymer or the native tissue. We found that the temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This technique, which was originally developed to stop bleeding by coagulating the proteins in the tissue, is very effective for the adhesion of materials such as polymers and metals to tissue because the heat and pressure applied to the materials and the tissue enables bonding by a mechanism similar to that of protein coagulation as mentioned above . We found that this principle could be used to develop a new device for achieving adhesion between materials and tissue . However, not all materials can be bonded with tissue in this way.…”
Section: Introductionmentioning
confidence: 99%
“…This technique, which was originally developed to stop bleeding by coagulating the proteins in the tissue, is very effective for the adhesion of materials such as polymers and metals to tissue because the heat and pressure applied to the materials and the tissue enables bonding by a mechanism similar to that of protein coagulation as mentioned above . We found that this principle could be used to develop a new device for achieving adhesion between materials and tissue . However, not all materials can be bonded with tissue in this way.…”
Section: Introductionmentioning
confidence: 99%